The Interplay of Psychological Empowerment and Workplace Spirituality in Shaping Organizational Citizenship Behaviour - Ismail, Fadillah; Bano, Yasmeen (JBS Nexus, 2024)
Malaysia as a developing country is also living in a fast-paced business environment, it can be difficult for companies to create and enforce regulations that motivate their staff. Employee engagement is widely seen as crucial to workers’ productivity in the office. Without enthusiastic participation from workers, companies will fail to achieve the goals of their business strategies, which are essential if they want to boost their performance. This research investigates the level of organizational citizenship behaviour and determines the effect between psychological empowerment and workplace spirituality towards organizational citizenship behaviour among employees at ABC Sdn Bhd. The effects are organizational citizenship behaviour leading to compulsory citizenship behaviour which also causes burnout among employees, unhealthy rivalry among employees and less productivity in a workplace. For this purpose, a questionnaire-based survey was conducted among 112 employees from several levels of management. The responses were analysed by mean and median, frequency and percentage by using Statistical Package for the Social Science (SPSS) software. The findings of this research could help stakeholders to be benefited from understanding the effects of psychological empowerment and workplace spirituality on organizational citizenship behaviour (OCB) in several ways. These benefits include improved organizational performance, increased employee engagement, enhanced organizational culture, improved employee well-being, and increased employee retention and loyalty. When stakeholders are aware of these effects, they can actively promote and support initiatives that foster psychological empowerment and workplace spirituality, leading to positive outcomes for both the organization and its employees.